Why INR is outside the therapeutic range in patients with acuteischemic stroke and atrial fibrillation - Elyar Sadeghi Hokmabadi; Sheida Shaafi; Yalda Sadeghpour; Reza Deljavan; Javad Jalili; Morteza Ghojazadeh; Elyar Alizade Najmi; Saeid Charsouei; Mehdi Farhoudi (Journal of Research in Clinical Medicine, 2022)
Introduction: Warfarin is still the primary drug used to prevent vascular events in patientswith atrial fibrillation (AF), especially in low-income countries. Therapeutic failure and non-adherenceare common causes of recurrent embolic events. The aim of this study was toinvestigate possible reasons why INR was outside the therapeutic range in patients presentingwith acute ischemic stroke and AF. Methods: This prospective study was performed over a ten-month period and all patientsadmitted with acute ischemic stroke were enrolled. Patients with AF who did not have INRwithin the therapeutic range (INR = 2-3) at the time of admission were identified. During a face-to-face interview, the reasons for INR being outside the therapeutic range were assessed basedon a prepared checklist. Results: During the study period, 810 patients had an acute ischemic stroke, of which 177 hadAF heart rhythm (22%). The median age was 76 (IQR: 71-83), and 87 (52%) were male. Of these177 patients, 44 (25%) had a previous history of AF ("previous AF" group) and 133 (75%) werediagnosed with AF during the current hospital admission ("new AF" group). Among patients onwarfarin but with INR outside the therapeutic range (29 in all), 20 (69%) did not see a physicianregularly and/or did not take medication according to the physician’s instructions. Conclusion: The most common reason for INR being outside the therapeutic range was patientslack of awareness of their heart disease (unrecognized AF). Other reasons included irregularvisits to the physician and drug non-adherence.